Peritoneal dialysis peritonitis due to Neisseria: clinicopathological features of 10 patients with a review of the literature - Yue Sun; Xinyu Chen; Jun Ni; Jin Yu (Renal Failure)
Background Peritoneal dialysis-associated peritonitis (PDAP) frequently arises as a complication in patients undergoing peritoneal dialysis. However, the understanding of the role of Neisseria, a gram-negative coccus, in PDAP is limited.Methods This study retrospectively analyzed data for patients with Neisseria-associated PDAP who were treated at our center from January 2010 to June 2022. These patients were classified into the Neisseria group (Group N) and matched 1:2 by sex, age, dialysis duration, and residual kidney Kt/V with a coagulase-negative staphylococci group (Group CNS) and a Staphylococcus aureus group (Group S) as controls. Statistical analysis was conducted via SPSS 25.0 and was supplemented with a review of the relevant literature, to investigate clinical features, pathways of infection, and patient outcomes.Results This study included 10 cases of Neisseria-associated PDAP, comprising 6 male and 4 female patients. The patients had an average age of 58.10 ± 14.52 years, and the average duration of peritoneal dialysis was 72.00 ± 46.99 months. Among these patients, 3 had first-time infections, while 7 had a prior history of PDAP. After treatment, 9 patients achieved medical cure, and 1 patient was transferred to hemodialysis (HD). Baseline comparisons across the 3 groups indicated notable differences in body temperature upon admission, which were statistically significant (p < 0.05), with patients in Group S having higher body temperatures compared to Group N and Group CNS. Compared with Group N, Group S presented a markedly elevated high-sensitivity C-reactive protein (hs-CRP) level, decreased serum albumin levels, reduced serum potassium levels, whereas Group CNS presented a significantly lower neutrophil percentage (N%) than did Group N (p < 0.05). Although survival analysis did not reveal statistically significant differences due to the limited sample size, Kaplan–Meier curves indicated a trend toward lower cure rates and slightly worse long-term outcomes in Group S than in Group N and Group CNS, with the latter 2 groups showing similar results.Conclusion Neisseria-associated PDAP generally has favorable outcomes, similar to those of CNS-related PDAP and better than those of S-related PDAP. Hypoalbuminemia, hypokalemia and elevated hs-CRP are key risk factors affecting outcomes, emphasizing the need to address them during treatment.